The Effectiveness of the Nobangan Learning Model Based on the Traditional Kaili Tribe Game on Students' Learning Interest - Azizah Thalib; Melyani Sari Sitepu; Herlina Herlina; Rizal Rizal; Atira Permata Delima (Universitas Pendidikan Ganesha, 2022)
The monotonous learning done by the teacher affects the students' low interest in learning. Students become indifferent and not diligent in following the learning process. This study aims to analyze the effectiveness of the Nobangan learning model based on the traditional game of the Kaili tribe on interest in learning in sixth grade elementary school students. This research uses Quasi Experiment method with Nonequivalent Control Group Design. The population and sample in this study amounted to 17 grade VI elementary school students. The data collection method used a questionnaire technique. The instrument of data collection was in the form of a questionnaire measuring students' interest in learning. Data analysis used paired sample t-test. Based on the results of the study showed that the Nobangan learning model was effectively used in increasing student interest in learning. So it can be concluded that the Nobangan learning model based on the traditional game of the Kaili tribe is effectively used to increase student interest in learning. The nobangan learning model is a learning model that begins with seeking information from the material or pictures that the teacher provides and then strengthens mastery of the material with the task of making questions and answers. At the end of the lesson, the information that has been obtained is recalled through the game of nobangan.